Development of a sustainable and innovant hygrothermal bio-composite featuring the enhanced mechanical properties. (20th August 2019) - Ahmad, Muhammad Riaz; Chen, Bing; Haque, M. Aminul; Ali Shah, Syed Farasat
Abstract: In this study, machine controlled high compaction force was used to produce an innovant, sustainable and energy efficient bio-composite based on magnesium phosphate cement (MPC) as binder and corn stalk as bio-aggregate. Characterization of corn stalk was investigated by water absorption, image processing, scanning electron microscopy (SEM), x-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) analysis. Mechanical, hygrothermal, aging and microstructural properties of bio-composites were examined. Compressive strength of bio-composites compacted by the machine was considerably higher than the manually compacted bio-composites. Capillary absorption and water absorption of bio-composites were lowered due to high compaction force. Increase in the temperature slightly affected the thermal properties of bio-composites. All the bio-composites were rated from good to excellent hygric regulators based on their moisture buffer performance. Influence of high compaction on the thermal, hygric and moisture buffer properties of bio-composites was discernible. Development of molds was detected on the specimens subjected to higher relative humidity level. Finally, formulated energy-efficient and sustainable bio-composites were classified into structural and insulation grade concrete.